PENINGKATAN KETERAMPILAN MENULIS TEKS PIDATO MELALUI MODEL PEMBELAJARAN KONTEKSTUAL PADA SISWA KELAS VII MTs AN-NUR TAHUN PELAJARAN 2023/2024 - Moh Ari Wibowo; Barrotul Qomariyah; Sahrul Muzekki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2024)
Writing skills are very important skills in life, not only in educational life but also very important in social life. Writing skills are taught with the aim that students are able to write well and correctly, therefore writing is called a productive and expressive activity. Therefore, the researcher raised the title